Colonial Fault Lines: First Nations Autonomy and Indigenous Lands in the Time of COVID-19 - Flynn, Alexandra; Shanks, Signa Daum (Allard Research Commons, 2022)
The COVID-19 crisis has exposed the political and economic fault lines in the exercise of power across multiple jurisdictions. This article focuses on the power of First Nations to make enforceable decisions in respect to reserve lands, specifically the powers First Nations have to enforce public health restrictions during the pandemic. We argue that Canadian law both enables First Nations to assert decisionmaking in respect to their lands, and undermines Indigenous authority in relation to enforcement and intergovernmental status. This paper is part of the SPE Theme on the Political Economy of COVID-19.